Human ANP32A/B are SUMOylated and utilized by avian influenza virus NS2 protein to overcome species-specific restriction - Liuke Sun; Xing Guo; Mengmeng Yu; Xue-Feng Wang; Huiling Ren; Xiaojun Wang (Nature Communications)
Abstract Human ANP32A/B (huANP32A/B) poorly support the polymerase activity of avian influenza viruses (AIVs), thereby limiting interspecies transmission of AIVs from birds to humans. The SUMO-interacting motif (SIM) within NS2 promotes the adaptation of AIV polymerase to huANP32A/B via a yet undisclosed mechanism. Here we show that huANP32A/B are SUMOylated by the E3 SUMO ligase PIAS2α, and deSUMOylated by SENP1. SUMO modification of huANP32A/B results in the recruitment of NS2, thereby facilitating huANP32A/B-supported AIV polymerase activity. Such a SUMO-dependent recruitment of NS2 is mediated by its association with huANP32A/B via the SIM-SUMO interaction module, where K68/K153-SUMO in huANP32A or K68/K116-SUMO in huANP32B interacts with the NS2-SIM. The SIM-SUMO-mediated interactions between NS2 and huANP32A/B function to promote AIV polymerase activity by positively regulating AIV vRNP-huANP32A/B interactions and AIV vRNP assembly. Our study offers insights into the mechanism of NS2-SIM in facilitating AIVs adaptation to mammals.